Stochastic and Equitable Distributed Energy-Efficient Clustering (SEDEEC) for heterogeneous wireless sensor networks. (3rd January 2011) - Elbhiri, B.; Saadane, R.; Aboutajdine, D.
The hierarchical clustering technique reduces strongly direct transmissions which consumes hardly the nodes energy. Many new protocols are specifically designed for wireless sensor networks using this strategy, where the objectives are to save energy and extend the network's lifetime. Adapting this approach, we propose a more equitable and stochastic technique which distributes uniformly the energy consumed trough the whole network using a dynamic probability to elect the Cluster Head (CH). This protocol is used for more energy efficiency distribution where the BS is localised far away from the network. Moreover, it is used where the collect data defines the maximum or the minimum values in supervised region. Simulation results show that our protocol enlarges the network lifetime and performances results compared to the Low-Energy Adaptive Clustering Hierarchy (LEACH), the Distributed Energy-Efficient Clustering (DEEC) and the Equitable Distributed Energy-Efficient Clustering (EDEEC).